2016
DOI: 10.1016/j.cognition.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Language supports young children’s use of spatial relations to remember locations

Abstract: Two experiments investigated the role of language in children’s spatial recall performance. In particular, we assessed whether selecting an intrinsic reference frame could be improved through verbal encoding. Selecting an intrinsic reference frame requires remembering locations relative to nearby objects independent of one’s body (egocentric) or distal environmental (allocentric) cues, and does not reliably occur in children under 5 years of age (Nardini, Burgess, Breckenridge, & Atkinson, 2006). The current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 26 publications
3
60
1
Order By: Relevance
“…Our findings also contribute to understanding the relation between spatial language and spatial thinking. Several studies have shown that spatial language helps spatial thinking and performance on many spatial tasks (e.g., Dessalegn & Landau, ; Loewenstein & Gentner, ; Miller, Patterson, & Simmering, ). Analysis of parental verbal and gestural spatial input and how children's individual characteristics relate to the quantity and quality of this input offers us venues to improve children's performance on spatial tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also contribute to understanding the relation between spatial language and spatial thinking. Several studies have shown that spatial language helps spatial thinking and performance on many spatial tasks (e.g., Dessalegn & Landau, ; Loewenstein & Gentner, ; Miller, Patterson, & Simmering, ). Analysis of parental verbal and gestural spatial input and how children's individual characteristics relate to the quantity and quality of this input offers us venues to improve children's performance on spatial tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated links between spatial language and spatial cognition across a range of spatial tasks, using both correlational and experimental designs (e.g., Dessalegn & Landau, , ; Hermer‐Vazquez, Moffet, & Munkholm, ; Loewenstein & Gentner, ; Miller, Patterson, & Simmering, ; Pruden, Levine, & Huttenlocher, ; Pyers, Shusterman, Senghas, Spelke, & Emmorey, ; but see Nardini, Burgess, Breckenridge, & Atkinson, ; Ratliff & Newcombe, for exceptions). One proposed explanation for these findings is that spatial language supports children's encoding of spatial features and relations, thus facilitating their performance on spatial tasks (e.g., Hermer‐Vazquez et al., ; Pruden et al., ).…”
Section: Current Studymentioning
confidence: 99%
“…Children's production of spatial words has been shown to be positively associated with their spatial skills (e.g., Hermer‐Vazquez et al., ; Miller et al., ; Pruden et al., ; Simms & Gentner, ). For example, children's production of particular spatial words, such as “left” and “right” at 5–6 years of age (Hermer‐Vazquez et al., ) or “middle” at 3–5 years of age (Simms & Gentner, ), is correlated with their performance on spatial tasks that depended on representing those relations.…”
Section: Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to clear developmental improvement, wide individual variation also was evident. Production of bi-referential spatial terms is especially challenging for English-speaking preschool-aged children (Weist et al, 1999), so more research is needed to understand the processes by which children come to produce complex spatial language that is precise and consistent and the implications of spatial language for other aspects of development (Miller, Patterson, & Simmering, 2016).…”
Section: Complex Spatial Language 25mentioning
confidence: 99%